Potentiating Virus-like Particles for Mucosal Vaccination Using Material Science Approaches - Milad Radiom (Colloids and Interfaces)
Virus-like particles (VLPs) exhibit such unique colloidal and structural properties that make them ideal candidates for various bio-nanotechnology applications, among which mucosal vaccination is particularly promising. However, since mucosal surfaces present harsh environments to VLPs, stabilization of VLP capsids or alternative delivery strategies are necessary. Addressing these challenges requires interdisciplinary research, and the intersection of material science and immunology is presented in this review. Approaches such as crosslinking capsid coat proteins, incorporating VLPs in polymer matrices and hydrogels, or forming crystalline nano-/micro-structures show potential for developing muco-stable VLP vaccines or for delivering these vaccines in a sustainable manner. This review explores recent material science approaches that leverage VLPs as nanotools for various applications and with the potential for translation to mucosal vaccination.